Effects of Demographic Factors on Grade-12 Mathematics Learners’ Receptiveness to Siyavula Educational Application - Ntuthuko Xulu; Joshua ABAH; Admire Chibisa; Anilkumar Krishnannair (International Journal of Instructional Technology and Educational Studies)
This empirical study deploys a partial least squares structural equation modelling (PLS-SEM) to investigate the effects of Demographic factors such as gender, location and usage duration on Grade-12 mathematics learners’ receptiveness to Siyavula Educational Application (SEA), a learning managements system (LMS) for basic schools in South Africa. The sample comprises 272 Learners in uMhlathuze circuit of King Cetshwayo District. Three of the sample schools are located in urban areas while the other three are located in rural areas. The study extended the Technology Acceptance Model (TAM) by conceptualizing perceived accessibility (PA), perceived social influence (PSI), perceived skill readiness (PSR) and computer self-efficiency (CSE), thereby developing a new integrated model (SEATAM) designed to understand the actual use of SEA by grade 12 Mathematics learners. Analysis of the results indicates that three pathways (Attitude Towards Technology effect on Actual Usage, Perceived Social Influence effect on Attitude Towards Technology, and Perceived Usefulness effect on Actual Usage) are affected by gender; two pathways (Attitude Towards Technology effect on Actual Usage, and Perceived Usefulness effect on Actual Usage) are affected by the residential location variable; and that hours spent has no significant effect on learners’ receptiveness to SEA. The implications of the findings were discussed with a recommendation for cogent LMS designs that can conveniently help rural students to be academically competitive with their urban counterparts. This study contributes further insights to the field of new technology usage, user acceptance research, LMS receptiveness, and information systems in its development of the SEATAM model.